Anti-Inflammatory and Analgesic Activity of Musa balbisiana Peels In Vivo - Ni Made Dwi Sandhiutami; Sondang Khairani; Rika Sari Dewi; Zainur Rahman Hakim; Anita Rahmi Pradani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Musa balbisiana Peels (MBP) contains high levels of flavonoids, alkaloids, tannins, saponins, and triterpenoids. Flavonoids function to slow down the inflammatory process by inhibiting the arachidonic acid, forming prostaglandins, and releasing histamine. This study aimed to examine the anti-inflammatory and analgesic effects of MBP decoction. This study used the Winter method for anti-inflammatory assay by induction of carrageenan on the soles of rat's feet and Sigmund's method for analgesic assay with intraperitoneal induction of acetic acid in mice. Group I as a negative control, group II as a positive control with diclofenac sodium, group III as a low dose (200 mg/kg BW of MBP), group IV as a medium dose (400 mg/kg BW of MBP), and group V as a high dose (800 mg/kg BW of MBP decoction). The percentage of inhibition in the anti-inflammatory test in rats for groups II, III, IV, and V was 34.43%, 17.68%, 25.53%, and 25.4%, and the percentage of effectiveness for the anti-inflammatory test, respectively, was 51.35%, 74.15%, and 74.01%. The results of the percentage inhibition of the analgesic test in mice for groups II, III, IV, and V were 55.25%, 38.52%, 44.53%, and 49.31%, and the percentage of effectiveness for the analgesic test, respectively, followed by 69.71%, 80.59%, and 89.24%. Based on the results, it can be concluded that the decoction of the MBP has an anti-inflammatory and analgesic effect.